ANALISIS KETIMPANGAN KEMAMPUAN PENERIMAAN PAJAK MENGGUNAKAN INDEKS WILLIAMSON PADA KABUPATEN DAN KOTA DI SUMATERA BARAT - Tilawatil Ciseta Yoda, Tilawatil Ciseta Yoda; Rina Febriani, Rina Febriani (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
West Sumatra as one of the provinces in Indonesia that accepted the government policy of regional autonomy. Regional autonomy in Indonesia is a form of decentralization. Regional autonomy is directed to accelerate regional independence in order to realize community welfare. The implementation of fiscal decentralization which has been implemented for approximately 15 years has significantly grown the regional economy of each regency / city, but on the other hand the inequality that occurs between districts / cities has also increased especially on tax revenues. One of the methods to assess tax revenues inequality of a region is to use the Williamson’s Index. This research aims to evaluate, describe and maping the level of inequality of tax revenues using theWilliamson’s Index between districts, cities and between districts and cities in West Sumatra Province for the period 2014-2016. The research was conducted in all districs and Cities in West Sumatra Province. The method of data analysis is by analyzing tax revenues using tax ratio, then the results are analyzed using the Williamson Index. Theresults showed; 1) Analysis of inter-districs tax ratio in West Sumatra in the 2014-2016 period was at an average of 0.12% in the low category, 2) Analysis of inter-cities tax ratio in West Sumatra for the period 2014-2016 was at an average of 0.28% with the medium category, 3) The results of the analysis of the inter-districs and cities tax ratio in WestSumatra for the 2014-2016 period were at an average of 0.18% in the low category, 4) The analysis of tax revenues with Williamson’s Index of inter-district tax ratio for the 2014- 2016 period showed Moderate category, 5) The analysis of tax revenues with Williamson’s Index of inter-cities tax ratio for the 2014-2016 period showed inequality category, 6) Theanalysis of tax revenues between districs and Cities with the Williamson Index in 2014-2016 period showed very inequality results. It is suggested to government of all districts and cities in West Sumatra to optimize tax potential by exploring the potential of the region they have, and sets target and tax rates so that tax revenue can be obtained maximally.